2021
DOI: 10.1021/acsapm.1c00398
|View full text |Cite
|
Sign up to set email alerts
|

Polyether-Based Block Co(ter)polymers as Multifunctional Lubricant Additives

Abstract: A series of polyether-based diblock copolymers were synthesized by sequential organocatalytic ring-opening polymerization (ROP) of either hexene oxide (HO) or octene oxide (OO) as the first monomer with propylene oxide (PO) as the second monomer. In addition, one triblock terpolymer of OO, PO, and styrene oxide (SO) was synthesized following the same method. The ROP was catalyzed by triethyl borane (TEB)/(phosphazene base t-BuP2) with eicosanol as the initiator. The resulting co­(ter)­polymers have a low polyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…21 Polyether based co(ter)polymers were also synthesized by a research group and reported as multifunctional polymeric compounds to investigate VI, anti-wear, antifriction, thermal stability and rheological activities as lubricant additives. 27 In view of the above discussion, the demand for polymeric multifunctional additives is continuously escalating, by embedding the inhibiting, cleaning, and suspending properties along with the excellent viscositytemperature relationship. So in present work, efforts have been made towards the copolymer synthesis of acrylates (C8, C12, and C18) and maleic anhydride through polymerization pathway, which further successfully coupled with the N-phenyl-p-phenylenediamine through amide linkage to reflect the inhibiting, detergent-dispersant activities along with the viscosity modifier and lowtemperature fluidity in lubricant BO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Polyether based co(ter)polymers were also synthesized by a research group and reported as multifunctional polymeric compounds to investigate VI, anti-wear, antifriction, thermal stability and rheological activities as lubricant additives. 27 In view of the above discussion, the demand for polymeric multifunctional additives is continuously escalating, by embedding the inhibiting, cleaning, and suspending properties along with the excellent viscositytemperature relationship. So in present work, efforts have been made towards the copolymer synthesis of acrylates (C8, C12, and C18) and maleic anhydride through polymerization pathway, which further successfully coupled with the N-phenyl-p-phenylenediamine through amide linkage to reflect the inhibiting, detergent-dispersant activities along with the viscosity modifier and lowtemperature fluidity in lubricant BO.…”
Section: Introductionmentioning
confidence: 99%
“…N ‐vinyl imidazole, N ‐vinylpyrrolidones, vinyl pyridines, and N , N ‐dialkylaminoethyl‐methacrylates grafted monomers units were successfully copolymerized with alkyl methacrylates and studied the application as lubricant multifunctional additives 21 . Polyether based co(ter)polymers were also synthesized by a research group and reported as multifunctional polymeric compounds to investigate VI, anti‐wear, antifriction, thermal stability and rheological activities as lubricant additives 27 …”
Section: Introductionmentioning
confidence: 99%
“…Olefin copolymers of chain length C 3 –C 10 successfully grafted with N‐arylphenylenedianine, aminothiazole, aminocarbazole, aminoindole, aminopyrrole, amino imidazolinone, amino‐mercapto triazole, and aminoperimidine to introduce multifunctionality for imparting effective viscosity index, dispersing, and anti‐oxidant properties during lubricant formulation 17 . Recently, polyether‐based di‐block (either hexene oxide or octene oxide as the first monomer with propylene oxide) and tri‐block (octene oxide, propylene oxide, and styrene oxide) polymers as multifunctional additives were prepared to examine the thermal stability, rheological and tribological study for lubricant application 18 . To introduce engine cleanliness behavior in the copolymer of octadecene‐maleic anhydride, different types of alcohols (dodecyl, hexadecyl, octadecyl, and docosanol) and amines (dodecyl amine, hexadecyl amine, and octadecyl amine) were successfully coupled.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, polyether-based di-block (either hexene oxide or octene oxide as the first monomer with propylene oxide) and tri-block (octene oxide, propylene oxide, and styrene oxide) polymers as multifunctional additives were prepared to examine the thermal stability, rheological and tribological study for lubricant application. 18 To introduce engine cleanliness behavior in the copolymer of octadecene-maleic anhydride, different types of alcohols (dodecyl, hexadecyl, octadecyl, and docosanol) and amines (dodecyl amine, hexadecyl amine, and octadecyl amine) were successfully coupled.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 One of the most prominent organic catalysts for ROP is the combination of Lewis base t-BuP 2 with Lewis acid triethylborane (TEB). 29,30 This Lewis pair organic catalyst shows very high polymerization efficiency and good control/selectivity on the ROP of cyclic ethers and cyclic esters. In addition, the alteration of the t-BuP 2 /TEB molar ratio allows us to realize facile one-pot block copolymerizations in both ether-first and ester-first orders, either by sequential monomer addition or from mixed monomers.…”
Section: ■ Introductionmentioning
confidence: 99%